Effectiveness of interventions for improving timely diagnosis of breast and cervical cancers in low and middle-income countries: a systematic review protocol - Fiona M Walter; Jennifer Moodley; Chukwudi Arnest Nnaji; Paul Kuodi (BMJ Open)
Introduction Breast and cervical cancers pose a major public health burden globally, with disproportionately high incidence, morbidity and mortality in low- and middle-income countries (LMICs). The majority of women diagnosed with cancer in LMICs present with late-stage disease, the treatment of which is often costlier and less effective. While interventions to improve the timely diagnosis of these cancers are increasingly being implemented in LMICs, there is uncertainty about their role and effectiveness. The aim of this review is to systematically synthesise available evidence on the nature and effectiveness of interventions for improving timely diagnosis of breast and cervical cancers in LMICs.Methods and analysis A comprehensive search of published and relevant grey literature will be conducted. The following electronic databases will be searched: MEDLINE (via PubMed), Cochrane Library, Scopus, CINAHL, Web of Science and the International Clinical Trials Registry Platform (ICTRP). Evidence will be synthesised in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). Two reviewers will independently screen the search outputs, select studies using predefined inclusion criteria and assess each included study for risk of bias. If sufficient data are available and studies are comparable in terms of interventions and outcomes, a meta-analysis will be conducted. Where studies are not comparable and a meta-analysis is not appropriate, a narrative synthesis of findings will be reported.Ethics and dissemination As this will be a systematic review of publicly available data, with no primary data collection, it will not require ethical approval. Findings will be disseminated widely through a peer-reviewed publication and forums such as conferences, workshops and community engagement sessions. This review will provide a user-friendly evidence summary for informing further efforts at developing and implementing interventions for addressing delays in breast and cervical cancer diagnosis in LMICs.PROSPERO registration number CRD42020177232.